A null variant in the apolipoprotein L3 gene is associated with non-diabetic nephropathy. Issue 2 (20th February 2017) - Skorecki, Karl L; Lee, Jessica H; Langefeld, Carl D; Rosset, Saharon; Tzur, Shay; Wasser, Walter G; Shemer, Revital; Hawkins, Gregory A; Divers, Jasmin; Parekh, Rulan S; Li, Man; Sampson, Matthew G; et al.
Abstract: Background: Inheritance of apolipoprotein L1 gene ( APOL1 ) renal-risk variants in a recessive pattern strongly associates with non-diabetic end-stage kidney disease (ESKD). Further evidence supports risk modifiers in APOL1 -associated nephropathy; some studies demonstrate that heterozygotes possess excess risk for ESKD or show earlier age at ESKD, relative to those with zero risk alleles. Nearby loci are also associated with ESKD in non-African Americans. Methods: We assessed the role of the APOL3 null allele rs11089781 on risk of non-diabetic ESKD. Four cohorts containing 2781 ESKD cases and 2474 controls were analyzed. Results: Stratifying by APOL1 risk genotype (recessive) and adjusting for African ancestry identified a significant additive association between rs11089781 and ESKD in each stratum and in a meta-analysis [meta-analysis P  =  0.0070; odds ratio (OR) = 1.29]; ORs were consistent across APOL1 risk strata. The biological significance of this association is supported by the finding that the APOL3 gene is co-regulated with APOL1, and that APOL3 protein was able to bind to APOL1 protein. Conclusions: Taken together, the genetic and biological data support the concept that other APOL proteins besides APOL1 may also influence the risk of non-diabetic ESKD.